Sinkhole occurrence and evolution, and seawater intrusion in a low-coastal setting of Apulia - Liso, Isabella Serena (Italian journal of engineering geology and environment, 2024)
In the last decades, the scientific community has paid an increasing attention on coastal karst areas, since these are highly urbanized and populated, and attract high number of tourists. This transition zone where anthropogenic, terrestrial, and marine processes simultaneously act, is intrinsically fragile, and its vulnerability to geological hazards is enhanced by the mixing between fresh and salt waters, causing a stronger dissolution on carbonate rocks. In this paper, a case study located along the coastal karst of Apulia, between the provinces of Bari and Brindisi, in one of the most touristic areas of the Region is described. In detail, this manuscript deals with description sinkholes evolution at the coastal zone and seawater intrusion in coastal aquifer. The case study highlights the influence of sinkholes in the modification of coastal geomorphology, potentially leading to natural hazards in terms for communities, urbanized land, and infrastructures. The geological setting presents the Cretaceous limestone bedrock overlain by more recent Cenozoic calcarenites and Quaternary marine terrace deposits. The topography is controlled by structural discontinuities, mainly oriented in SW-NE direction. This area is locally defined "Costa Merlata", which means "Merlon coast", as it resembles the merlons of a medieval castle. This is due to a strong control exerted by sinkholes in the genesis of bays and inlets. In fact, in this stretch of the Adriatic coastline, it is possible to observe important freshwater outflows, including the main spa of central Apulia (Torre Canne spa), and several evidence of sinkholes, including recent collapse at a few meters from the coastline. The morphologic evolution is characterized by different phases: individual openings of sinkholes, which evolve to small inlets showing the larger sinkhole inland, accompanied by minor openings toward the sea; the last phase is characterized by well-developed bays, deriving from coalescence of sinkholes, overall entering inland for some tens of meters, by means of progressive failures, also favored by sea-storms. In addition to the sinkhole hazards, the area is affected by inland seawater intrusion. In fact, the hydrogeological setting of the coastal stretch, extending for about 25 km, shows evidence of groundwater salinization, with salinity values ranging from 0,5 g/l to more than 5 g/l. The springs with high discharge rate are in the sand dunes zone (Fiume Grande, Fiume Piccolo, and Fiume Morello) and discharge hundreds of liters of freshwater per second, while several diffuse springs, often with unknown discharge, are submerged. In such complex zone, caves adopted as groundwater monitoring spots, especially near the sea, where fresh water and sea water meet. The latter is also carried out by monitoring of stygofauna, i.e. animal species living exclusively within groundwater. Stygofauna can be considered environmental indicator and natural tracer, since it is highly sensitive to environmental variation; therefore, studying groundwater ecosystems will allow to characterize the groundwater quality and the main freshwater pathways.